Google map and canva for spatial understanding of grade 12 social studies students of SMAN 1 Warung Kiara, Sukabumi District - Enshanty, Yulia (Journal of Environment and Geography Education, 2024)
Background: Land use planning is a fundamental aspect of the Geography education for high school students, involving the organization of geographical space across economic, social, and cultural dimensions. A comprehensive grasp of this subject is imperative for students to comprehend the optimal utilization and management of geographical space. Methods: This study investigates the efficacy of Google Maps satellite mode and Canva as instructional tools for land use planning among senior high school students at SMAN 1 Warung Kiara, Sukabumi Regency. Google Maps satellite mode provides visual representations of planning areas, while Canva facilitates the creation of visually appealing and comprehensible land use planning designs. A descriptive quantitative approach was employed, involving questionnaires and interviews with a purposive sample of 32 students. Findings: The findings indicate that 75% of a students found learning with Google Maps satellite mode and Canva to be more engaging and comprehensible compared to traditional methods. Conclusion: Interviews further revealed an enhancement in students' understanding of land use planning concepts following exposure to these media. The utilization of Google Maps satellite mode and Canva emerges as an effective instructional strategy for enhancing students' comprehension of land use planning, underscoring the potential of technology and visual design in geography education.